Out-of-field dose in stereotactic radiotherapy for paediatric patients. (July 2021) - Garrett, Lachlan; Hardcastle, Nicholas; Yeo, Adam; Lonski, Peta; Franich, Rick; Kron, Tomas
Highlights: Small field measurements were performed in a paediatric anthropomorphic phantom using thermoluminescence dosimetry. The study confirmed the reduction of out-of-field dose using flattening filter free beams in complex geometries. Dose beyond 40 cm from the field edge is mostly determined by leakage and independent of field size. Abstract: Background and purpose: Stereotactic radiotherapy combines image guidance and high precision delivery with small fields to deliver high doses per fraction in short treatment courses. In preparation for extension of these treatment techniques to paediatric patients we characterised and compared doses out-of-field in a paediatric anthropomorphic phantom for small flattened and flattening filter free (FFF) photon beams. Method and materials: Dose measurements were taken in several organs and structures outside the primary field in an anthropomorphic phantom of a 5 year old child (CIRS) using thermoluminescence dosimetry (LiF:Mg, Cu, P). Out-of-field doses from a medical linear accelerator were assessed for 6 MV flattened and FFF beams of field sizes between 2 × 2 and 10 × 10 cm 2 . Results: FFF beams resulted in reduced out-of-field doses for all field sizes when compared to flattened beams. Doses for FFF and flattened beams converged for all field sizes at larger distances (>40 cm) from the central axis as leakage becomes the primary source of out-of-field dose. Rotating the collimator to place the MLC bank in the longitudinal axis of the patient was shown to reduce the peripheral doses measured by up to 50% in Varian linear accelerators. Conclusion: Minimising out-of-field doses by using FFF beams and aligning the couch and collimator to provide tertiary shielding demonstrated advantages of small field, FFF treatments in a paediatric setting.